Fluorescence markers in some New Zealand honeys. (1st February 2016) - Bong, Jessie; Loomes, Kerry M.; Schlothauer, Ralf C.; Stephens, Jonathan M.
Highlights: Manuka ( Leptospermum scoparium ) and kanuka ( Kunzea ericoides ) fluoresced. Other New Zealand honeys examined did not fluoresce. Two marker excitation–emission wavelengths each were identified for manuka and kanuka honeys. Dilution of manuka and kanuka honeys reduced fluorescence proportionally. Abstract: The fluorescence characteristics of various New Zealand honeys were investigated to establish if this technique might detect signatures unique to manuka ( Leptospermum scoparium ) and kanuka ( Kunzea ericoides ) honeys. We found unique fluorescence profiles for these honeys which distinguished them from other New Zealand honey floral types. Two excitation–emission (ex–em) marker wavelengths each for manuka and kanuka honeys were identified; manuka honey at 270–365 (MM1) and 330–470 (MM2) nm and kanuka honey at 275–305 (KM1) and 445–525 (KM2) nm. Dilution of manuka and kanuka honeys with other honey types that did not possess these fluorescence profiles resulted in a proportional reduction in fluorescence signal of the honeys at the marker wavelengths. By comparison, rewarewa ( Knightia excelsa ), kamahi ( Weinmannia racemosa ), and clover ( Trifolium spp.) honeys did not exhibit unique fluorescence patterns. These findings suggests that a fluorescence-based screening approach has potential utility for determining the monoflorality status of manuka and kanuka honeys.